2017
DOI: 10.1111/jpn.12678
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moringa oleifera leaves as a substitute for alfalfa meal on nutrient digestibility, growth performance, carcass trait, meat quality, antioxidant capacity and biochemical parameters of rabbits

Abstract: SummaryThis contribution reports the effects of Moringa oleifera leaves (MOLs) meal on the growth performances, nutrient digestibility, carcass trait, meat quality, antioxidant capacity and biochemical parameters of growing New Zealand white rabbits. The MOL was substituted for alfalfa meal at levels of 0, 10%, 20% and 30% to obtain respective diets MOL0, MOL10, MOL20 and MOL30. Each treatment was replicated five times with 10 rabbits per replicate. Results showed the average daily weight gain (ADWG) and feed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 41 publications
(56 reference statements)
6
29
0
1
Order By: Relevance
“…On the other hand, herein, the HDL level was significantly increased in the rabbits that received the PLM diets ( p = 0.037), but LDL was decreased ( p = 0.042) in those that received 30% PLM. Our findings are partially consistent with those of Sun et al [42], who detected that the inclusion of 10% tree foliage in rabbit diets resulted in the lowest value of serum LDL when compared with the alfalfa group. These effects could be linked to the PLM antioxidant and antiperoxide activity [4] or the reduction of energy intake [43].…”
Section: Resultssupporting
confidence: 93%
“…On the other hand, herein, the HDL level was significantly increased in the rabbits that received the PLM diets ( p = 0.037), but LDL was decreased ( p = 0.042) in those that received 30% PLM. Our findings are partially consistent with those of Sun et al [42], who detected that the inclusion of 10% tree foliage in rabbit diets resulted in the lowest value of serum LDL when compared with the alfalfa group. These effects could be linked to the PLM antioxidant and antiperoxide activity [4] or the reduction of energy intake [43].…”
Section: Resultssupporting
confidence: 93%
“…Many studies have demonstrated that diets supplemented with Moringa oleifera leaf meal or extract improved the meat quality by, for example, increasing the meat pH and water‐holding capacity in goats, broilers and pork (Hazra, Biswas, Bhattacharyya, Das, & Khan, ; Mukumbo, ; Qwele, ). Rabbit fed with 10% Moringa oleifera leaf meal could decrease the meat drip loss and the shear force of the longissimus dorsi (Sun et al, ). This decrease might be attributed to the quercetin in Moringa by assisting in the prevention of meat degradation by oxidation (Lin et al, ; Moyo, Masika, Hugo, & Muchenje, ).…”
Section: Discussionmentioning
confidence: 99%
“…level of lipid peroxidation in animals (Xi et al, 2016). Also, Sun et al (2017) reported that the 20% Moringa oleifera leaves substitu- Values that differ significantly at P < .05.…”
Section: The Consumption Ofmentioning
confidence: 95%